2021
DOI: 10.1080/01443410.2021.1954601
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital, future-oriented coping, and the well-being of secondary school teachers in Germany

Abstract: Data availability statement:The data that support the findings of this study are available on request from the corresponding author. The data are not publicly available as there is no ethical approval to do so as participants did not provide appropriate consent to do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 58 publications
1
15
0
1
Order By: Relevance
“…As stated above, previous studies have confirmed that there is a positive association between PsyCap and positive emotions such as job satisfaction ( Luthans et al, 2007 ) and psychological well-being ( Ganotice et al, 2016 ; Huang and Zhang, 2021 ; Mikus and Teoh, 2021 ) and a negative correlation between PsyCap and negative emotions such as job stress ( Narsa and Wijayanti, 2021 ) and burnout ( Freire et al, 2020 ; Barratt and Duran, 2021 ; Wang et al, 2021a ). However, the question remains unsettled as to whether PsyCap would lead to more enjoyable online teaching experience.…”
Section: Literature Reviewsupporting
confidence: 52%
See 1 more Smart Citation
“…As stated above, previous studies have confirmed that there is a positive association between PsyCap and positive emotions such as job satisfaction ( Luthans et al, 2007 ) and psychological well-being ( Ganotice et al, 2016 ; Huang and Zhang, 2021 ; Mikus and Teoh, 2021 ) and a negative correlation between PsyCap and negative emotions such as job stress ( Narsa and Wijayanti, 2021 ) and burnout ( Freire et al, 2020 ; Barratt and Duran, 2021 ; Wang et al, 2021a ). However, the question remains unsettled as to whether PsyCap would lead to more enjoyable online teaching experience.…”
Section: Literature Reviewsupporting
confidence: 52%
“…It has been found that PsyCap positively predicted the psychological well-being and happiness of university teachers ( Li, 2018 ; Kun and Gadanecz, 2022 ), and helps them thrive in career development ( Liu et al, 2021 ). Three of the four dimensions of PsyCap, namely optimism, hope, and resilience were also proved to have a significant impact on secondary school teachers’ job satisfaction ( Mikus and Teoh, 2021 ). No study to date, however, has examined whether there is a relationship between teachers’ PsyCap and teaching enjoyment in the context of online teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, research confirmed that hope levels were positively associated with positive coping styles, including positive reappraisal, planning, acceptance, and fighting spirit. Positive coping mediates not only self-compassion and life satisfaction, but also self-efficacy and work engagement ( Dunkley et al, 2016 ; Li et al, 2021 ; Mikus and Teoh, 2021 ). Those studies highlighted the importance of positive coping in promoting hope and life satisfaction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, teacher well-being, which is rooted in positive psychology, has received special attention in teacher training programs ( Mikus and Teoh, 2021 ). Recent studies show that people have four different types of well-being: emotional, spiritual, physical, and mental or intellectual.…”
Section: Review Of Literaturementioning
confidence: 99%